The effectiveness of operating the AIDS activities for youths in education institutes, years 2009-2011 - จิรโรจนวัฒน รวิสรา; เปี่ยมวัฒนาทรัพย์ อภิญญา; รองศรีแย้ม นุชนาฎ (Disease Control Journal, 2018)
The objective of this research is to study the effectiveness of perception of AIDS activities for youth’ร education institute es, Chonburi Province and lesson distilled AIDS intervention activities and evalu¬ation youth’s satisfaction towards participation. Including to area expansion in other education institutes. The study is the quasi-experiment research of One group Pretest-Postest design. The samples are 867 youth’s education institutes. Data was analyzed by quantitative and qualitative methods. The results showed that the better knowledge and attitude towards AIDS. Also, they had right understanding more than the day before and had statistically significant of (p<0.001). And increase rate of using condoms in most recent times when they had sexual relation with the heterosexual couples of statistically significant of (p<0.05). Lesson distilled found that the conceptual of driving activities by network-teams can give out that youths in each education institutes and use kinds of activities. Therefore strategies of working as network-teams are important. There are not enough to change of their youth’s behavior. In addition unreadiness and lack of potential sex-education of teachers. The activities was emphasized on the process more than the results themselves, lack of integra¬tion in each dimension, therefore youth-leaders and teachers would not continuously setting the activities if it was not agreed or contingent to the policy, budget and knowledge or network-teams. Analyzed these process found that some activities were lack of youth’s participation, follow up then enabled to the quality and not strongly enough to achieve long term goal. Designed for the programs suitable for perception, the change responsibility of in-change during the process should be aware not to happen as that would cause learning not continually. The qualification of youth-leaders must be clear. Good relationship and support would make the projects to succeed. Result of project showed better health behavior and got to learn, be model as well, develop skills and knowledge sharing from other institutes. They had knowledge and high satisfaction to further developments. Therefore, organizing learning activities, teachers’potential and supportments will be effect on youths to change their health behavior.